Effect of Plasmonic Gold Nanoprisms on Biofilm Formation and Heat Shock Proteins Expression in Human Pathogenic Bacteria - Rihab Lagha; Fethi Ben Abdallah; Amine Mezni; Othman M. Alzahrani (MDPI AG, 2021)
Gold nanoparticles have gained interest in biomedical sciences in the areas of nano-diagnostics, bio-labeling, drug delivery, and bacterial infection. In this study, we examined, for the first time, the antibacterial and antibiofilm properties of plasmonic gold nanoprisms against human pathogenic bacteria using MIC and crystal violet. In addition, the expression level of GroEL/GroES heat shock proteins was also investigated by western blot. Gold nanoparticles were characterized by TEM and EDX, which showed equilateral triangular prisms with an average edge length of 150 nm. Antibacterial activity testing showed a great effect of AuNPs against pathogenic bacteria with MICs values ranging from 50 μg/mL to 100 μg/mL. Nanoparticles demonstrated strong biofilm inhibition action with a percentage of inhibition ranging from 40.44 to 82.43%. Western blot analysis revealed that GroEL was an AuNPs-inducible protein with an increase of up to 66.04%, but GroES was down-regulated with a reduction of up to 46.81%. Accordingly, plasmonic gold nanoprisms, could be a good candidate for antibiotics substitution in order to treat bacterial infections.